Measuring the Impact of Certification on Kindergarten Teacher Performance: An Empirical Comparative Study - Meifarina, Whyesi; Rakimahwati; Yaswinda; Nurhafizah Nurhafizah (Institut Agama Islam Negeri Madura, 2025)
The performance of Kindergarten teachers is not optimal and the ownership of certification is not evenly distributed in Bukit Sundi Subdistrict. The purpose of this research is to: (1) describe the performance of certified and non-certified teachers, and (2) analyze the performance differences between the two. The research uses a mixed-method approach with a sequential exploratory design. Data analysis techniques include instrument testing, descriptive analysis, classical assumption testing, and hypothesis testing. The research population consists of all kindergarten teachers in the Bukit Sundi District, with the sample determined through simple random sampling using the Slovin formula. The data collection instruments include questionnaires, observations, and documentation. The results show that the performance of certified teachers falls into the very good category (86.7%), while non-certified teachers only reach 39.9%. Hypothesis testing indicates a significant difference between the two groups (p < 0.05). These findings indicate that certification has a significant impact on improving the performance of kindergarten teachers. This study recommends the need for enhanced training and certification programs to support the quality of early childhood education.